Code switching, code mixing, and language attitude in Arabic village (observational study on Arabic course of Al Azhar, Pare, Kediri, Indonesia) - Binti Khoiriyah; Syihabuddin; Mohamad Zaka Al Farisi (Indonesian Reseacher for Language Learning and Teaching, 2024)
The phenomenon of bilingualism that often occurs is a lot of code-switching or code-mixing, both in learning and outside learning. This phenomenon also occurs in the Arabic village, exactly in an Arabic course. The aims of this study are (1) to compare the forms of code-switching and code-mixing in learning and outside learning and (2) to reveal the language attitudes of respondents and the causes of code-switching and code-mixing. This research uses a descriptive-comparative method with an observational study design. The results show that three forms of external code-switching were found in one learning period (one month), ten forms of external code-mixing, and one form of internal code-mixing. Outside of learning, one form of internal code-switching, two forms of external code-switching, and three forms of external code-switching are found. In learning, code-switching is caused by familiarity, annoyance, and formality, while code-mixing is caused by the speaker’s first language, prestigious, language habit, and language limitation. Outside of learning, code-switching is caused by relax situation, familiarity, and assumption, while language habit and relax situation cause code-mixing. Code-switching and code-mixing relate to the attitude of respondents language towards Arabic, which is in the high category with a percentage of 79.42%.